Medicinal ethnobotany in Huacareta (Chuquisaca, Bolivia) - Quiroga Rodrigo; Meneses Lidia; Bussmann Rainer W (BMC, 2012)
Abstract Background The aim of this study was to document the types of diseases treated by the use of medicinal plants, their main applications and also to have a report of the major diseases treated at the Hospital of San Pablo de Huacareta (Chuquisaca Bolivia). Methods We conducted semi-structured interviews on the use medicinal plants with 10 local informants, and categorized the kinds of diseases treated by traditional medicine. We obtained reports of cases treated at the Hospital of Huacareta in order to compare the use frequency of traditional medicine and allopathic medicine for the treatment of recurrent diseases in the area. Results Our survey identified 258 traditional medicine uses, spanning a total of 13 diseases categories and including 91 native and exotic plant species and one unidentified sample plant type. Gastrointestinal disorders (55%) were most frequently treated with medicinal plants, followed by afflictions of the musculoskeletal system (25%) and dermatological disorders (24%). Hospital information indicates that the most common diseases are acute respiratory infections (47%) and acute diarrheal diseases (37%). The herbal remedies were mostly used in the form of teas and decoctions. The informants used mainly native plant species, although exotic species has been introduced to the pharmacopoeia. Conclusions The treatment of gastrointestinal disorders is the primary objective of the medical ethnobotany of the inhabitants of Huacareta, while respiratory system diseases are mostly treated in the hospital. Looking at the data from the Hospital records we can infer that gastrointestinal disorders are among the most common diseases in the study area. For most respondents, traditional medicine is a reliable choice for the care of their illnesses. However, the preference of the population for either traditional medicine or allopathic medicine needs to be clarified in future comparative studies to obtain more convincing results. The results presented can be used as a base for subsequent work related to traditional medicine and its contribution to allopathic medicine in San Pablo de Huacareta. Resumen Introducción El objetivo del presente estudio fue documentar los tipos de enfermedades tratadas mediante el uso de plantas medicinales, sus aplicaciones principales y también tener un reporte de las enfermedades mayormente atendidas en el Hospital de San Pablo de Huacareta (Chuquisaca, Bolivia). Métodos Se realizaron encuestas semiestructuradas a 10 informantes locales anotando los usos atribuidos a sus plantas medicinales, se agruparon las plantas por categorías de enfermedades tratadas en la medicina tradicional. Se obtuvieron reportes de casos tratados en el Hospital de Huacareta para poder relacionar el tratamiento de enfermedades recurrentes en la zona entre la medicina tradicional y la medicina occidental. Resultados Se reportaron 91 especies nativas y exóticas, además de un espécimen indeterminado exótico que intervienen en un total de 258 aplicaciones medicinales, las cuales son empleadas en un total de 13 categorías de enfermedades. Los desórdenes gastrointestinales (55%) son mayormente tratados mediante plantas medicinales, seguidas de las afecciones al sistema esqueleto-muscular (25%) y enfermedades dermatológicas (24%). La información del Hospital indica que las enfermedades más frecuentes son Infecciones Respiratorias Agudas (47%) y Enfermedades Diarreicas Agudas (37%). Los remedios vegetales se emplean en forma de infusiones y cocciones principalmente. Se emplean mayormente plantas nativas, también se introdujo en la farmacopea médica el uso de plantas exóticas al lugar. Conclusiones El tratamiento de trastornos gastrointestinales constituye el objetivo primordial de la etnobotánica médica de los habitantes de Huacareta, las enfermedades del sistema respiratorio, son mayormente tratadas en el Hospital. Observando los datos del libro de consultas del Hospital, se puede inferir que los desórdenes gastrointestinales están entre las enfermedades más frecuentes en el área estudiada. Para la mayoría de los entrevistados, la medicina tradicional es una opción confiable para la atención de sus enfermedades. Sin embargo, la preferencia de los habitantes entre la medicina tradicional y la medicina alopática podría ser clarificada a partir de futuros estudios comparativos que permitan obtener resultados más convincentes. Los resultados expuestos pueden ser usados como una base de datos para posteriores trabajos relacionados a la medicina tradicional y su contribución con la medicina alopática en San Pablo de Huacareta.